2014
DOI: 10.1049/el.2014.2092
|View full text |Cite
|
Sign up to set email alerts
|

71% PAE C‐band GaN power amplifier using harmonic tuning technology

Abstract: A high-efficiency C-band internally matched power amplifier, developed with 12 mm AlGaN/GaN high-electron mobility transistors is described. The second-harmonic frequency (2f 0) tuning network is applied to confine the impedance at 2f 0 in safe efficiency regions. The packaged power amplifier achieves 71% power-added efficiency (PAE) and 102 W output power, associated with 17 dB power gain. The PAE is believed to be the highest of the C-band GaN power amplifiers reported to date. power of more than 92 W. At 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…This technique is very promising for the fabrication of high-quality GaN thin film that can be physically detached from the sapphire. The domain boundaries are not related to crystallographic planes, but when the polarity domain was switched oppositely from Ga-to N-polarity, domain boundaries are more preferentially formed on the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) planes, possibly due to the propagation of the growth front consisting of juxtaposed opposite polar Process schematic used to create periodically oriented III-nitride materials. First, a buffer layer is deposited.…”
Section: Fabrication Of Lps On Sapphire Substratementioning
confidence: 99%
See 1 more Smart Citation
“…This technique is very promising for the fabrication of high-quality GaN thin film that can be physically detached from the sapphire. The domain boundaries are not related to crystallographic planes, but when the polarity domain was switched oppositely from Ga-to N-polarity, domain boundaries are more preferentially formed on the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) planes, possibly due to the propagation of the growth front consisting of juxtaposed opposite polar Process schematic used to create periodically oriented III-nitride materials. First, a buffer layer is deposited.…”
Section: Fabrication Of Lps On Sapphire Substratementioning
confidence: 99%
“…In the past few decades, there has been intensive investigation in the area of III-nitride wide bandgap materials including InN, GaN, AlN, and their ternary, quaternary alloys [1][2][3][4]. The unique properties of adjustable direct bandgaps, high break down field, high saturation velocity, good thermal conductivity and resistance to harsh environment conditions make III-nitride materials ideal candidates for various kinds of applications, including solid-state lighting and displays [5,6], photodetectors for radar systems and medical diagnostics [7,8], power electronics used in automobiles, railway systems, and consumer electronics [9,10], and 5G communications [11].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Kim et al [7] manufactured S-band 69.9% PAE class-F and 69.4% PAE inverse class-F power amplifiers. We also increased the PAE of the GaN-based internally-matched power amplifier to 71% at 4 GHz [8] and 69% at 5.5 GHz. [9] At X-band applications, Resca et al [10] reported a GaN MMIC power amplifier with 38% PAE for future generation synthetic aperture radar (SAR) systems.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Amplifiers, transmitter/receiver T/R modules and radars based on GaN devices are less complex, with output power density, gain, efficiency and reliability improved. [3][4][5][6] In recent years, many two-stage power amplifiers based on GaN HEMT have been reported. Although they have achieved splendid performances, the power added efficiency PAE is less than 50% and the associated power gain is less than 25 dB.…”
Section: Introductionmentioning
confidence: 99%